Erythroleukemia Presenting as Non-immune Haemolytic Anemia: A Rare Presentation - Gupta, Aastha (Springer India, 2014)
Non-immune haemolysis is a rare manifestation of acute leukaemia and more so in acute myeloid leukemia. Here, we report a case of non-immune and non-fragmentation haemolysis as the initial presenting manifestation in a 55-year-old female with acute myeloid leukaemia (AML-M6). All other potential aetiologies of haemolysis were excluded, including drugs, paroxysmal nocturnal haemoglobinuria, immune and other known congenital and acquired causes of haemolytic anaemia. This case shows that malignant haematopoietic disorders should be considered in patients with newly diagnosed haemolysis.